2000
DOI: 10.1097/00001756-200011270-00054
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of glial cell line-derived neurotrophic factor (GDNF) following traumatic spinal cord injury

Abstract: We investigated the temporal and spatial expression patterns of the GDNF gene after subjecting rats to an acute contusion injury of the spinal cord using the weight drop technique. Reverse transcriptase-polymerase chain reaction (RT-PCR) revealed that GDNF transcription in the spinal cord began to increase within 30 min after injury and peaked within 3 h. Immunohistochemical analysis showed GDNF immunoreactivity to be present mainly in microglia and macrophages 1 day after injury, but not in neurons or astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 6 publications
6
44
0
1
Order By: Relevance
“…5A). This finding is in agreement with previous data showing an increase in GDNF secretion by activated EMÈ (37)(38)(39)(40).…”
Section: Emès Induce Pda Migration By Secretion Of Gdnf and Activatiosupporting
confidence: 94%
“…5A). This finding is in agreement with previous data showing an increase in GDNF secretion by activated EMÈ (37)(38)(39)(40).…”
Section: Emès Induce Pda Migration By Secretion Of Gdnf and Activatiosupporting
confidence: 94%
“…Our data indicated that grafted NIH3T3-TG persisted and secreted GDNF in the injured spinal cord 3 wk after transplantation. An immediate upregulation of GDNF transcript after SCI followed by an increase in its protein expression in microglia and macrophages 1 d after injury have been reported (31), suggesting that endogenous GDNF could provide neuronal protection after the insult. GDNF detected 3 wk after transplantation was most likely secreted by the engrafted NIH3T3-TG cells.…”
Section: Discussionmentioning
confidence: 89%
“…Up-regulation of GDNF by astrocytes or microglial cells occurs in several injury models (Liberatore et al, 1997;Batchelor et al, 1999;Bresjanac and Antauer, 2000;Satake et al, 2000;Wei et al, 2000;Miyazaki et al, 2001;Ikeda et al, 2002;Marco et al, 2002;Hashimoto et al, 2005a). This switch in the production of GDNF from neurons to glial cells may provide a local mechanism to limit neuronal loss and promote regeneration.…”
Section: Gdnf Expression Upon Nigrostriatal Injury: Role Of Neuronglimentioning
confidence: 99%